MENGOPTIMALKAN BIAYA PRODUKSI UNTUK MEMAKSIMALKAN PROFITABILITAS USAHA COOKIES “KUKISS” - Rebecca Kezia; Rini Tri Hastuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
The culinary business is a sector with promising profit prospects, but its success depends heavily on operational efficiency. The key to achieving this efficiency lies in the ability to accurately calculate and manage food costs. This article analyzes the application of these principles to